Multicolor up conversion emission and color tunability in Yb3+/Tm3+/Ho3+ triply doped heavy metal oxide glasses - Ledemi, Yannick [UNESP]; Manzani, Danilo [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Messaddeq, Younes [UNESP] (Elsevier B.V., 2011)
Multicolor and white light emissions have been achieved in Yb3+, Tm3+ and Ho3+ triply doped heavy metal oxide glasses upon laser excitation at 980 nm. The red (660 nm), green (547 nm) and blue (478 nm) up conversion emissions of the rare earth (RE) ions triply doped TeO2-GeO2-Bi2O3-K2O glass (TGBK) have been investigated as a function of the RE concentration and excitation power of the 980 nm laser diode. The most appropriate combination of RE in the TGBK glass host (1.6 wt% Yb2O3, 0.6 wt% Tm2O3 and 0.1 wt% Ho2O3) has been determined with the purpose to tune the primary colors (RGB) respective emissions and generate white light emission by varying the pump power. The involved infrared to visible up conversion mechanisms mainly consist in a three-photon blue up conversion of Tm3+ ions and a two-photon green and red up conversions of Ho3+ ions. The resulting multicolor emissions have been described according to the CIE-1931 standards. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Bismuth tellurite glasses; Rare earth ions; Up conversion fluorescence; Multicolor emission; Color tunability